L’ENSEIGNEIMENT A DISTANCE PAR TELEVISION DANS LE CONTEXTE DU COVID-19. CAS DES ECOLES DE LA VILLE DE BUKAVU EN REPUBLIQUE DEMOCRATIQUE DU CONGO. CONSEILS PRATIQUES AUX USAGERS. - Bienvenu, KASIMU IDI (IJRDO- Journal of Educational Research, 2024)
The self-managementand the autonomy of learnerss mustbe taken into accountWhen developing plansdistance and teaching learning todistance.Before COVID-19, learning programs distance targeted mainadult learnerscompetentself-management or young people learnings with daccompanying persons. During theCovid-19, however, the appTarget distance retentionhasPPrevents at all stages.Programs to APPROGDistance homehave multiple dEFIS to students with regard toconcerns their habits oflearning and their masteryself, their motivation, leuRS Relations with their parentsas well as their projects ofcome. The fact that the routinesdailydisturbed, in particular, canrequirein place rigorous hoursseparated for eachactivity and often generatea pace of learningslower. Electronicselectronic (telephonemobile, television etc.),require self-control skills that students may not haveR Acquired. For students to remain involvedS sans the presence of teachers, theycount potenon parents formotivate them and manage yourNT that badly their activitieslearning, which cancause tensionin famil relationshipsiales. In addition, according to the age of the learners, the incrementTudging of the situation in hisTogether can causeanxietyAs for the passage in the upper class.On the other hand, study at homeby means of televisionoffers agood opportunity to learnerss d’Improve their skills inself-management. Comprehealth andCOVID19 security, become an autonomous personand active and ensure his IBEN-being can be part ofskills to acquire, dyears the framework of learningthroughout life